2011
DOI: 10.3390/polym3031181
|View full text |Cite
|
Sign up to set email alerts
|

Microspheres Containing Cibacron Blue F3G-A and Incorporated Iron Oxide Nanoparticles as Biomarker Harvesting Platforms

Abstract: Abstract:In this work, magnetic functionality was introduced to cross-linked acrylamide-based particles via the in situ coprecipitation of iron oxide nanoparticles within the hydrogel particle interior. Cibacron Blue F3G-A was then incorporated onto the magnetic hydrogel scaffold to facilitate the harvest of targeted protein species. The dye-loaded magnetic particles were physically characterized, and their protein sequestration performance was investigated. The results of these studies indicated that dye-load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Hydrogels were used several times for valves, [16][17][18][19][20][21] pores, [22][23][24][25][26][27] lters 28,29 or chemical storing. [30][31][32] In previous studies it was shown that smart hydrogels can be used to fabricate micro-pores, 27 chemically tuned lters for biomolecule size exclusion as well as biomarker harvesting 28,29 and membranes with temperature dependent permeation properties. 26,[33][34][35][36][37][38][39][40][41][42] To alter the separation features of hydrogel based micropores or biomarker harvesters the hydrogels can be chemically or physically modied.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels were used several times for valves, [16][17][18][19][20][21] pores, [22][23][24][25][26][27] lters 28,29 or chemical storing. [30][31][32] In previous studies it was shown that smart hydrogels can be used to fabricate micro-pores, 27 chemically tuned lters for biomolecule size exclusion as well as biomarker harvesting 28,29 and membranes with temperature dependent permeation properties. 26,[33][34][35][36][37][38][39][40][41][42] To alter the separation features of hydrogel based micropores or biomarker harvesters the hydrogels can be chemically or physically modied.…”
Section: Introductionmentioning
confidence: 99%
“…The microgels were synthesized using the inverse miniemulsion polymerization technique. In general, nanogel and microgel particle formation can be achieved by different approaches including precipitation polymerization from aqueous or polar solutions, cross‐linking of preformed polymers and oligomers in emulsions, or copolymerization of different water‐soluble monomers and cross‐linkers in inverse (W/O) emulsion, microemulsion or miniemulsion systems . Since microgel preparation based on inverse miniemulsion polymerization enables the equal distribution of all components in each particle, it is advantageous compared with other methods when homogenous gel properties and an equal distribution of all different functionalities are desirable.…”
Section: Introductionmentioning
confidence: 99%